PANDANGAN MASHLAHAH MURSALAH TERHADAP PERKAWINAN SECARA PERJODOHAN DI LINGKUNGAN MASYARAKAT ( Studi Kasus Di Desa Joho Kecamatan Pace Kabupaten Nganjuk ) - Ulfaturrosidah Ulfaturrosidah; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract This thesis discusses the analysis of Mashlahah on Arranged Marriage in the Community Environment of the Village District, Nganjuk Regency. with 2 sub-problems, namely first how is the process of arranged marriage in Joho Village, Pace District, second, what are the factors that cause Arranged Marriage in the Community Environment of Joho Village, Pace District. With the aim of knowing the phenomenon and form of arranged marriage and analyzing the values of mashlahah towards the attitude of arranged marriage in Pace District, Nganjuk Regency. This research is field research, namely research with data obtained from field activities. The data obtained in this study through interviews and documentation with the aim of obtaining definite data. Furthermore, it was analyzed using descriptive methods, with an inductive mindset. The data was analyzed using general theories of mashlahah mursalah related to the matchmaking process. The results of the study show that: 1) the matchmaking process that occurs in society today occurs because of the hereditary culture, where matchmaking will continue to exist from time to time. Because basically matchmaking will still be carried out if the parents still have a sense of culture so that with the matchmaking it can strengthen good relations in the family and other relatives. 2) review of the problems of matchmaking, the relationship between the matchmaking process is essentially very beneficial for the people. As a result, there are many parties who take advantage of the existence of matchmaking among the people by educating themselves about matchmaking procedures that are in accordance with Islamic law. In addition, the practices carried out during the matchmaking period have met the requirements for benefits, namely being one language with the will of the sharia, providing benefits and concerning the interests of many people.